Utilizing quantitative measures of visceral adiposity in evaluating trauma patient outcomes. (September 2015) - Docimo, Salvatore; Lamparello, Brooke; Cohen, Melissa Fay; Kopatsis, Anthony; Vinces, Fausto
Abstract: Introduction: Body mass index (BMI) has commonly been used as a parameter to assess obesity in trauma patients. However, the variability of height and weight data in trauma patients limits the use of BMI as an accurate assessment tool in the trauma population. Quantitative radiologic measurements of visceral adiposity is an accurate method for assessing obesity in patients but requires further analysis before it can be accepted as a measurement tool for trauma patients. Methods: A retrospective review of trauma cases with pre-operative CT scan from 2008 to 2015 produced 57 patients for evaluation. Preoperative BMI was calculated using measured height (m2) and weight (kg). Radiologic measurements of adiposity were obtained from preoperative CT scans using OsiriX DICOM viewer software. Visceral fat areas (VFA) and subcutaneous fat areas (SFA) were measured from a single axial slice at the level of L4-L5 intervertebral space. Results: No statistically significant results were found relating visceral fat:subcutaneous fat ratios to length of stay or post-operative complications. Initial clinical observations noting an increased incidence of complications among patients with a V/S ≥ 0.4 demonstrates a possible link between obesity and poor outcomes in trauma patients. A statistically significant correlation was noted between length of stay, peri-nephric fat and injury severity score. Discussion and Conclusion: Our pilot study should be viewed as the foundation for a larger prospective study, utilizing quantitative measurements of visceral adiposity to assess outcomes in trauma patients. Highlights: Quantitative radiologic measures of visceral adiposity is the gold standard to assess obesity. This is the first attempt to associate V/S ratios with trauma outcome measurements. Clinical association of an increased V/S ratio and complications in trauma patients noted. Further prospective studies are required for further analysis.